Myanmar : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Myanmar. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Myanmar's economic growth remains strong, but macroeconomic imbalances have increased significantly over the past year. Real GDP growth for FY2014/15 (April-March) is estimated to have reached 8.5 percent. The fiscal deficit increased to 3 percent of GDP in FY2014/15, while credit to the private sector continued to grow strongly at 35 percent (year over year) in March, albeit lower than in FY2013/14. The current account deficit widened to more than 6 percent of GDP, largely reflecting a rapidly rising trade deficit. The Myanmar economy is set for strong growth in 2015 amid signs of overheating. The economy is expected to grow by 8.5 percent, reflecting strong growth momentum and expansionary macroeconomic policies.